DUCK: A Drone-Urban Cyber-Defense Framework Based on Pareto-Optimal Deontic Logic Agents - Deb, Tonmoay; Dix, Jürgen; Jeong, Mingi; Molinaro, Cristian; Pugliese, Andrea; Quattrini Li, Alberto; Santos, Jr, Eugene; Subrahmanian, V.S.; Yang, Shanchieh; Zhang, Youzhi (Proceedings of the AAAI Conference on Artificial Intelligence, 2024)
Drone based terrorist attacks are increasing daily. It is not expected to be long before drones are used to carry out terror attacks in urban areas. We have developed the DUCK multi-agent testbed that security agencies can use to simulate drone-based attacks by diverse actors and develop a combination of surveillance camera, drone, and cyber defenses against them.